Characterization of surface free energy of mineral filler by spreading pressure approach. (10th September 2019) - Zhang, Derun; Luo, Rong; Zeng, Zhe
Highlights: Propose a spreading pressure approach based on a generalized Washburn equation. Measure spreading pressure of reference liquid on mineral filler through vapor adsorption test. Determine specific surface area of mineral filler based on the modified BET model. Compute resultant effective capillary radius and spreading pressure of mineral filler based on capillary rise test results. Validate the proposed approach through a standard asphalt mastic moisture susceptibility test. Abstract: Surface free energy of mineral filler plays an important role in evaluating the adhesion of asphalt mastic (mineral filler plus asphalt binder), which is usually measured through the capillary rise approach. However, this approach has been verified to hold only for the low energy materials, which does not apply to the high energy mineral filler. To overcome this limitation, the paper devises a new approach for measuring the surface free energy of the mineral filler based on a generalized Washburn equation. First, a reference liquid is selected to conduct the vapor adsorption test on the mineral filler to measuring its spreading pressure, in which a modified Brunauer-Emmett-Teller (BET) model is employed to determine the filler specific surface area. This reference liquid is again used to perform the capillary rise measurement to calculate the resultant effective capillary radius of the filler bed. Three independent liquids are subsequently selected to conduct the capillary rise test to measure their spreading pressure values with respect to the same mineral filler. By substituting the measured spreading pressure values of the three liquids into the Good-van Oss-Chaudhury (GvOC) equation, the surface free energy components of the mineral filler are finally determined. This newly developed approach is then successfully applied to measure the surface free energy for four typical types of the mineral filler. The moisture susceptibility rankings obtained from the energy ratios of the proposed approach are experimentally found to be consistence with those measured from a standard moisture susceptibility test for the corresponding asphalt mastics. In this regard, the proposed approach is believed to be capable of accurately characterizing the surface free energy of the mineral filler.